Abundance and active patch selection modulate reproductive connectivity and fitness of pea crabs living on sand dollars - Souza, Juliana de Andrade (2021)
Connectivity is known to be an essential process contributing to the stability of local populations, but the mechanisms ruling the distribution of populated habitat patches and how these distribution patterns affect reproductive connectivity and, especially, the fitness of individuals remains elusive. Here, we focus on pea crabs that are obligatory commensals of sand dollars, that need to travel over unsuitable habitat (the sandy seabed) for host shifts. The distribution of occupied and vacant sand dollars was mapped, and the population structure in all sand-dollar hosts was assessed, at nine different sites. We found that habitat supply is high, not limiting the size of crab populations, but also that crab abundance poses limits to reproductive connectivity and thus the potential for offspring production. However, except for extreme cases of low and high connectivity, crab aggregations at sand-dollar clusters, countervailing the naturally random distribution of whole sand-dollar populations, greatly enhance the reproductive potential of whole populations at most sites. The gregarious behavior of pea crab populations is apparently mediated by the concentration of host and conspecific cues in the water, and by interactions among individuals in the sand-dollar environment, with larger females likely playing a more important role. Differently from the effects on population reproductive connectivity, crab abundance plays a dual indirect influence on individual fitness through contrasting connectivity effects. Individual fitness, measured only in females as the percent deviation from expected egg production, was found to be largely unaffected by connectivity, except at the sites where crab abundance was the lowest (positive effects) or the highest (negative effects). These results suggest that individual fitness remains high at intermediate crab densities, but decreases when crab abundance is too low, possibly limiting mate encounters and imposing sperm limitation for egg production, or too high, likely forcing breeding females to engage in negative interactions with conspecifics at the expense of reduced resource allocation to yolk accumulation. This study indicates that connectivity effects may be diversified and subtle, affecting different levels of biological organization in specific ways.